MOTIVES FOR NON-ADHERENCE OF CHILDREN TO THE VACCINATION CAMPAIGN AGAINST INFLUENZA - Josiane Steil Siewert; Dayane Clock; Poliana Giacomin Mergner; Patrícia Fernandes Albeirice da Rocha; Marceli Diana Helfenstein Albeirice da Rocha; Angela Maria Alvarez (Universidade Federal do Paraná, 2018)
Objective: get to know the reasons for non-adherence of parents/responsible caregivers of children to the vaccination campaign against influenza. Method: quantitative and descriptive research. Inclusion criteria: parents or responsible caregivers of children between six months and up to four years of age, living in the city of Joinville. Interviews were held with 380 responsible caregivers of children aged between six months and four years, using a semi-open questionnaire, in 2016, and the descriptive analysis was applied to the data. Results: the campaign reached the target, with 89% of the children being vaccinated. The reasons for non-adherence to the campaign were: fear of adverse reaction (21; 51.3%); information that the child had the flue (10; 24.3%); and not knowing about the campaign (5; 12.4%). Conclusion:nursing plays a fundamental role in the elaboration, planning and execution of vaccination campaigns. This study evidenced the need to improve the health education strategies concerning vaccination against the influenza virus and to broaden the access to Primary Health Care.